Cover Picture: Surface Segregation of Fe in Pt–Fe Alloy Nanoparticles: Its Precedence and Effect on the Ordered‐Phase Evolution during Thermal Annealing (ChemCatChem 22/2015). Issue 22 (November 2015) - Prabhudev, Sagar; Bugnet, Matthieu; Zhu, Guo‐Zhen; Bock, Christina; Botton, Gianluigi A.
Abstract : The Front Cover shows how to study a nanoscale phase transformation on a single nanoparticle level, by coupling both the heating capability, as well as advanced electron microscopy techniques, in situ. One single nanoparticle is annealed here, from initial (top right) to final (bottom left), the red‐hot holder shows the high temperature/heating, the time arrow shows dynamic measurements. The yellow beam represents an electron probe on the atomic level shining on a transition‐state particle, and scattered electrons are collected using various detectors. In their Full Paper, Prabhudev et al. demonstrate their in situ approach, which they believe is a step forward from the conventional approaches of studying phase transformation on nanoparticles, in general.